Experimental study of the efficiency of a SDD X-ray detector by means of PIXE spectra - Limandri, Silvina Paola (2013)
The efficiency of a silicon drift detector with ultrathin window was studied for energies between 0.27 and 25keV. Experimental values of the X-ray yields from samples of known stoichiometry were obtained by impact of 2 MeV protons. By using theoretical calculations of these yields the relative efficiency of the detector was evaluated. The results are compared with efficiency values obtained from the window transmission and the detector quantum efficiency. A quantitative analysis of a particle induced X-ray emission spectrum for a reference sample was performed in order to evaluate the consistency of the data presented in this work.